2023
DOI: 10.1101/2023.02.17.528996
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pulmonary osteoclast-like cells in silica induced pulmonary fibrosis

Abstract: The pathophysiology of silicosis is poorly understood, limiting development of therapies for those who have been exposed to the respirable particle. We explored the mechanisms of silica-induced pulmonary fibrosis in a mouse model using multiple modalities including whole-lung single-nucleus RNA sequencing. These analyses revealed that in addition to pulmonary inflammation and fibrosis, intratracheal silica challenge induced osteoclast-like differentiation of alveolar macrophages and recruited monocytes, driven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…In a murine model study, silica-induced pulmonary fibrosis was observed to stimulate osteoclast-like differentiation, leading to the recruitment of monocytes to the tissue. This process of osteoclast-like differentiation of alveolar macrophages is mediated by the osteoclastogenic cytokine RANKL, which is released from pulmonary lymphocytes and type II alveolar epithelial cells [49]. Collectively, these studies suggest the potential involvement of this mechanism in the persistent effects observed post-viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…In a murine model study, silica-induced pulmonary fibrosis was observed to stimulate osteoclast-like differentiation, leading to the recruitment of monocytes to the tissue. This process of osteoclast-like differentiation of alveolar macrophages is mediated by the osteoclastogenic cytokine RANKL, which is released from pulmonary lymphocytes and type II alveolar epithelial cells [49]. Collectively, these studies suggest the potential involvement of this mechanism in the persistent effects observed post-viral infection.…”
Section: Discussionmentioning
confidence: 99%